1001 Nights of Wonder in the Era of Harun al-Rashid (786–809) - Oktafianti, Dwi Rosita; Zahidiyah, Khakimatuz; Permatasari, Putri Ayu Diah (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
The history of 1001 Nights is the most popular anthology of Middle Eastern legends, which continued to flourish under the reign of Caliph Harun al-Rashid of the Abbasid Dynasty (786–809 AD). These stories were composed not only for entertainment but also as a reflection of the social, political, and cultural realities of the golden age of Islam.This study aims to explore the connection between the content of The Tale of 1001 Nights and the real-life experiences of society and the political policies of Harun al-Rashid. It also examines Harun al-Rashid’s establishment of Bayt al-Hikmah—an institution dedicated to the translation, preservation, and development of knowledge—and investigates how 1001 Nights mirrors the Islamic civilization of the time.The primary sources in this research include Husain Haddawy’s The Arabian Nights, Harun al-Rashid in Philip K. Hitti’s History of the Arabs, Harun al-Rashid and One Thousand and One Nights by André Clot, and translations of Alf Laila wa Laila from Arabic into various languages.